PENGEMBANGAN MAJALAH SEKOLAH VIRTUAL UNTUK MENINGKATKAN LITERASI PESERTA DIDIK DI KOTA DEPOK - Refisa Ananda; Nunung Supratmi; Syafruddin Syafruddin (STKIP Pesisir Selatan, 2022)
The school’s virtual magazine provide an opportunity for students to publish their writings. The development of virtual school magazines was carried out in 4 schools in Depok City, namely SMP and MA Madinatul Quran, SMK Bhakti Karya, and MTs. Al-Ittihad. This activity was carried out by utilizing the issues digital platform. The school's virtual magazine is published once a month. The school's virtual magazine is managed by the teacher and provided by the school as a forum for students' creativity. The writing rubrics provided in the virtual magazine are poetry, news, short stories, and photojournalism. Each school has 1 (one) issue account which is managed by the teacher as their virtual school magazine publishing platform for free.